(untitled) (UNWE Yearbook, 2024)
This article presents a methodology for the implementation of Digital competence framework (DigComp 2.1.), verified and approved in Bulgaria. DigComp is a critical tool to understand digital competence, to increase mobility and educational opportunities; to help empower individuals with digital skills, required to the needs of job market. This methodology is part of a national initiative for development of digital competences through the implementation of DigComp 2.1, which aims to overcome the imbalance between the digital knowledge and skills of the workforce.